Effects of psychological stress on skin and hair pigmentation in Polish adolescents - Sitek, Aneta; Żądzińska, Elżbieta; Rosset, Iwona (Anthropological Review, 2012)
The effects of psychological stress, gender and age on hair and skin pigmentation levels were evaluated in the reported study. The material included Polish high-school and university students aged 18–22 (in the age range 17.50–22.49). All subjects who had sunbathed or used tanning beds or lamps, skin tanning agents, tanning extenders and/or medical agents affecting skin pigmentation during the 60 days preceding the beginning of the study were excluded. The use of hormonal contraceptives within a month prior to the study was also an excluding factor. Stress levels were evaluated by the Perceived Stress Scale (PSS–10) in the Polish adaptation, while hair and skin pigmentation levels were assessed with a dermaspectrometer (Cortex Technology®, Denmark, 2007). The study was carried out with the exclusion of the summer period. Skin pigmentation was evaluated in 395 subjects (264 women and 131 men). Hair pigmentation was analyzed in a smaller group of 351 subjects (223 women and 128 men), as some had had their hair dyed within 12 months prior to the study while in some others the hair was too short to be correctly measured. Regardless of their age, the studied women felt much more stress related to their life situation and were characterized by stronger skin pigmentation than the examined men. No sex differences were identified with regard to hair pigmentation. In the studied period of ontogenesis (18–22 years of age), hair pigmentation levels increased with age, while skin melanization remained stable. Disregarding the effects of age and sex, the level of perceived stress was negatively correlated with skin pigmentation levels; no such relationship was found for hair melanization.